2006
DOI: 10.1099/jmm.0.46530-0
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of invasive Streptococcus pneumoniae in Taiwan, 2002–2003

Abstract: A total of 522 Streptococcus pneumoniae invasive isolates from diverse sources were collected from January 2002 to December 2003 in Taiwan in order to understand the serotype distribution of invasive isolates in Taiwan. The most frequently isolated serotypes of S. pneumoniae were types 14 (18?4 %), 23F (15?1 %), 3 (13?8 %), 19F (13?4 %), 6B (8?2 %), 9V (3?6 %) and 4 (2?5 %). The majority of cases were either under 5 years of age (24?1 %) or older than 65 years (36?6 %). Serotype distribution in adults aged ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…12,27 The most prevalent serotypes of invasive isolates also were attributed to these serotypes. 10,27 Therefore, the diversity of resistance patterns is limited.…”
Section: Discussionmentioning
confidence: 99%
“…12,27 The most prevalent serotypes of invasive isolates also were attributed to these serotypes. 10,27 Therefore, the diversity of resistance patterns is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwan Centers for Disease Control (TCDC) has implemented or participated in IPD surveillance projects since 2001 [ 28 40 41 ]. Health care facilities were encouraged to submit the clinical information of IPD cases and pneumococcal isolates to TCDC during the surveillance periods.…”
Section: Surveillance Of Ipd and Pcv Administrationmentioning
confidence: 99%
“…Fung had reported that 41.3%, 45.8%, and 63.3% of 550 clinical pneumococcal isolates were covered by PCV7, PCV13, and PPV23 in 1996-1997, respectively, when the pneumococcal vaccine has not been licensed in Taiwan [ 42 ]. Between 2001, when the PPV23 was introduced to the private sector in Taiwan, and 2005, when the PCV7 was introduced to the private sector in Taiwan, the surveillance reports showed a high coverage for PCV7, PCV13, and PPV23, except for Chen et al's report [ 41 ] which showed the coverage rate was 63.0% for PCV7 and 87.2% for PPV23 [ 43 44 45 46 ]. Most of the leading serotypes during this period were covered by the PCV7.…”
Section: Serotype Epidemiology Of Ipd In Taiwanmentioning
confidence: 99%
“…A recent study found that 80.7% of SP isolates from Taiwanese children younger than 14 years were penicillin resistant. Despite the implementation of stringent antibiotic-prescribing protocols, Taiwan has one of the highest rates of antibiotic-resistant SP in the world [5].…”
Section: Introductionmentioning
confidence: 99%